Mobile Web 2.0 : developing and delivering services to mobile devices - Mohammad Ilyas , 1953-; Syed A. Ahson (Auerbach Publications, 2011)
Covers various aspects of Mobile Web 2.0. This book identifies the main challenges and proposes a platform architecture that addresses some of these challenges, discusses different platforms for developing mobile services, and examines the effect of context on mobile usability